Residents perception toward squatter resettlement in Rumah Pangsa Limauan Kinarut, Papar / Mohd Salehan Selamat and Farah Dyana Rosly - Selamat, Mohd Salehan; Rosly, Farah Dyana (2015)
This research is conducted at Rumah Pangsa Limauan Jalan Safoda Kinarut, 89600 Papar Sabah where 150 respondents have involved. Rumah Pangsa Limauan Kinarut, Papar is a Squatter Resettlement for squatters in Sri Tanjung, Putatan. We will conduct research on resident's perception towards the effectiveness of squatter resettlements. Residents in the Rumah Pangsa Limauan Kinarut will be our respondent in order to get the information that can be used in our research. This section will discuss on differences among the sociodemographic factor (gender, age, marital status and races) of respondents on the perception towards squatter resettlements in Rumah Pangsa Limauan Kinarut. Our objectives are to determine resident's perception on squatter resettlements and to determine resident's perception on the effectiveness of squatter resettlement.